2015
DOI: 10.5888/pcd12.140377
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Secondhand Tobacco Smoke and Interventions Among Pregnant Women in China: A Systematic Review

Abstract: IntroductionSmoking prevalence is high among men in China. One result is that a large number of nonsmoking Chinese women may be exposed daily to secondhand smoke (SHS). Exposure is particularly problematic for pregnant women because of potential adverse reproductive effects. To determine the extent of this exposure and to summarize existing intervention studies designed to reduce SHS exposure in China, a systematic review of the literature published from 1995 through 2012 was conducted.MethodsWe searched the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 16 publications
0
75
7
1
Order By: Relevance
“…Out of the 37% (122) who reported presence of active smokers at home, 35.5% (114) have 1-2 smokers and the rest 3-5 smokers. Our study shows that even though there is high number of consumed cigarettes per day, most of the exposed pregnant reported exposure time of less than one hour, which is inconsistent with other studies that shows the more cigarettes consumed at home, the more hours of exposure reported (8,9). This can be due to either the participants and the active smokers have good knowledge about the harms of SHS exposure and they follow measures to avoid it or it could be due to under reporting by the participants of the real timing of exposure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Out of the 37% (122) who reported presence of active smokers at home, 35.5% (114) have 1-2 smokers and the rest 3-5 smokers. Our study shows that even though there is high number of consumed cigarettes per day, most of the exposed pregnant reported exposure time of less than one hour, which is inconsistent with other studies that shows the more cigarettes consumed at home, the more hours of exposure reported (8,9). This can be due to either the participants and the active smokers have good knowledge about the harms of SHS exposure and they follow measures to avoid it or it could be due to under reporting by the participants of the real timing of exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…The study did not measure cotinine level in the pregnant women blood, to see if they were telling the truth about their exposure to SHS. Another limitation was we did not specify whether the participants lived in rural or urban areas, as differences in the cultures and the socioeconomic characteristics have been confirmed in the literature (8)(9)(10). Also we did not assess the knowledge, attitude and behavior of the participants toward SHS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Rates are generally lower in Asia, Africa and the Middle East, though the rate approaches 15% in Turkey (6). While the rate of active smoking during pregnancy is low in China, exposure to second hand smoke while pregnant exceeds 50% (7). In England, the smoking during pregnancy rate is approximately 20% (8) and has unfortunately remained stable in recent years.…”
Section: Prevalence Of Smoking During Pregnancymentioning
confidence: 99%
“…For comparison, there are few, if any, other intervention research activities that have focused on reducing SHS exposure among adult nonsmokers; most of the previous SHS interventions have targeted children’s exposure, pregnant women (24,25), adult smoking cessation, hospitalized patients, or household smoking bans.…”
Section: Discussionmentioning
confidence: 99%